Technologies Applied to the Mental Health Care of Pregnant Women: A Systematic Literature Review - Carvalho, Laís Lage de; Teixeira, Júlia Magna da Silva; Unger, Roberto José Gervásio; Motti, Vivian Genaro; Lovisi, Giovanni Marcos; Grincenkov, Fabiane Rossi dos Santos (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective: This article aims to review the literature regarding the use of technologies to promote mental health for pregnant women. We seek to: understand the strategies that pregnant women use for mental health care. Also, we investigate the existence of scientific evidence that validates such practices.Methods: This study follows the PRISMA guidelines for systematic reviews. We analyze 27 studies published between 2012 and 2019. We include publications in Portuguese, English, and Spanish.Results: The results revealed several different possibilities to use technology, including the use of text messages and mobile applications on smartphones. Mobile applications are the most commonly used approaches (22.5%). Regarding the strategies used, cognitive-behavioral approaches, including mood checks, relaxation exercises, and psychoeducation comprised 44.12% of the content.Conclusion: There is a need for further investigation and research and development efforts in this field to better understand the possibilities of intervention in mental health in the digital age.
Keywords: Pregnancy; Telemedicine; Mental health; Prenatal care; Pregnancy complications